The Effect Of Motivation And Work Environment On Employee Job Satisfaction At Syekh Yusuf Regional General Hospital Gowa District - Syarif, Azmi Syauki; Akib, Haedar; Rivai, Andi Muhammad (Jurnal Administrasi Bisnis, 2026)
This study aims to examine the effect of motivation and work environment on employee job satisfaction at Syekh Yusuf Hospital, Gowa Regency. To achieve this goal, researchers use indicators to measure these variables. In the motivation variable, the indicators used are physiological needs, security needs, social needs, self-esteem needs and self-actualization needs. In the work environment variables, the indicators used are lighting/light in the workplace, temperature in the workplace, safety in the workplace and cleanliness. As for the job satisfaction variable, the indicators used are job, wages, promotions, supervisors and co-workers. In this research, the research method used is quantitative research, with data collection techniques carried out through observation, questionnaires and documentation. The sample used in this research was 87 respondents. Data obtained from research results were processed using data analysis and using the SPSS version 25 software program which consists of validity test, reality test, normality test, multiple linear regression analysis, and coefficient of determination. The results of this research indicate that motivation and work environment simultaneously have a significant influence on employee job satisfaction. Partially, motivation has a significant influence on employee job satisfaction, and the work environment partially has a significant influence on employee morale at Syekh Yusuf Hospital, Gowa Regency.